Effects of Moisture Content and Grain Type on Mechanical Properties of White Rice: Literature review and Experiment - Nursigit Bintoro; Alya Iqlima Zahra (Universitas Pendidikan Indonesia, 2022)
The mechanical properties of agricultural grains are required in the design of agricultural processes and machinery. These properties are influenced by moisture content and grain type. This study aimed to determine the effect of moisture content and grain type on the mechanical properties of white rice. There are three different types of white rice, namely short-bold (Koshihikari), long-medium (IR 64), and very long-slender (Basmati) grains within three levels of moisture content of 9%, 14%, and 19% were used as the samples in the experiment. The experiment was designed into Completely Randomized Design, factorial 3 x 3. The dimension, internal friction angle, and rupture force of the grain samples were respectively measured using a digital calliper, direct shear cell apparatus, and compression test apparatus. It could be concluded that moisture content, grain type, and the interaction of these two factors significantly affected almost all parameters of the mechanical properties of white rice. Most of the relationships between the parameters of mechanical properties and moisture content could be expressed as linear equations.